CONTAMINATION TEST OF SALMONELLA SP. IN HOUSEHOLD INDUSTRY WHITE TOFU NAIMATA KUPANG - Ni Nyoman Yuli (Wahana Matematika dan Sains: Jurnal Matematika, Sains, dan Pembelajarannya, 2020)
The test of Salmonella bacteria Sp. contamination . in white tofu produced in home industries in Naimata has been conducted.  The test was conducted at the Microbiology Laboratory of the Food and Drug Supervisory Agency of the Province of East Nusa Tenggara in Kupang on August 3 - August 8, 2016. The research based on the level of consumption of tofu produced in home industries in Naimata is quite high by the community. The purpose of this study was to determine whether the white tofu produced in the household industry in Naimata was contaminated with Salmonella bacteria or not. The research process consists of three stages, namely, the Pre-enrichment stage, where the sample is weighed 25 grams aseptically and then mixed into 225 mL BPW media and incubated at 37 ° C for 24 hours, enrichment stage is the stage where 1 mL of culture in the previous stage was taken and 0.1 mL was then added to the media so that MKTTn and RVS were 10 mL which were then incubated at 37 ° C and 42.5 ° C for 24 hours, the Inoculation and Identification stage was culture from MKTTn media and RVS was taken then planted in the media XLD and BGA specific. The data analysis method used is only comparing the test results from the research sample with SNI: 01-3142-1998 regarding the Quality Requirements of Tofu as a reference. This test is also made a positive comparison or control, which is also made XLD and BGA media planted with culture of Salmonella bacteria. The results of the ceramics test of Salmonella bacteria in white tofu stated that the white tofu produced in the home industry in Naimata was not contaminated with Salmonella bacteria Sp. with a negative value of colonies / 25 grams of samples according to the Indonesian National Standard SNI: 01-3142-1998 regarding the quality requirements of tofu.